ANALYZING THE FACTORS BEHIND CODE-SWITCHING BY PETRA CHRISTIAN UNIVERSITY’S ENGLISH DEPARTMENT STUDENTS - Wigati, Shintia Adiningsih; Puspo, Natasya Aurelia (Sanata Dharma University, Yogyakarta, 2023)
English Department students are encouraged to communicate in English, especially within the classroom. However, English is not their mother tongue; hence this leads to lack of English proficiency to support daily means of communication. This factor triggers the prevalence of code switching by the English Department students. The phenomenon also happens among Petra Christian University’s students. This paper would like to analyze the factors that encourage and the factors which discourage students to do code-switching using Braun Clarke’s (2006) analytical procedure. To obtain the necessary data, we distributed questionnaires related to code-switching phenomena to 47 students of Petra Christian University’s English Department and interviewed 21 of the selected respondents from both English for Creative Industry and English for Business majors. The questionnaire and interview questions inquired regarding the interlocutors and the factors which respectively encourage and discourage them to practice code switch. Findings indicate that communication efficiency, foreign language practice, habit, level of intimacy, and inability to translate English expressions to Indonesian encourage English Department students of Petra Christian University to perform code switching. Meanwhile, proficiency level, professionalism, avoiding potential misunderstanding, and level of intimacy discourage English Department students of Petra Christian University from performing code-switching.